2021
DOI: 10.1177/1179173x211004267
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Use Status as a Function of Transgender Identity: The Mediating Role of Psychological Distress

Abstract: Aim: The current study examined differences between individuals identifying as transgender and people identifying as cisgender in terms of (1) psychological distress (eg, anxiety, depression, and suicidal ideation), (2) rates of combustible and e-cigarette use, and (3) the potential for elevated psychological distress stemming from transgender identification to be associated with increased rates of smoking and vaping. Method: This was a secondary analysis of data from a study examining behavioral health, perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…In addition, similar findings were reported for transgender men from the BRFSS 2014-2016 (AOR, 1.86; 95% CI, 1.08-3.21) . These findings seem to be in line with other studies that examined community-based samples, including TGD youths . Other reports could not demonstrate differences in tobacco habits, as shown in a secondary analysis of the Population Assessment of Tobacco and Health study (AOR, 1.19; 95% CI, 0.75-1.89) and substudies of the BRFSS 2016 (AOR, 0.87; 95% CI, 0.54-1.41) and the BRFSS 2014 (AOR, 1.20; 95% CI, 0.84-1.72) .…”
Section: Cancer Risk Factorssupporting
confidence: 87%
See 4 more Smart Citations
“…In addition, similar findings were reported for transgender men from the BRFSS 2014-2016 (AOR, 1.86; 95% CI, 1.08-3.21) . These findings seem to be in line with other studies that examined community-based samples, including TGD youths . Other reports could not demonstrate differences in tobacco habits, as shown in a secondary analysis of the Population Assessment of Tobacco and Health study (AOR, 1.19; 95% CI, 0.75-1.89) and substudies of the BRFSS 2016 (AOR, 0.87; 95% CI, 0.54-1.41) and the BRFSS 2014 (AOR, 1.20; 95% CI, 0.84-1.72) .…”
Section: Cancer Risk Factorssupporting
confidence: 87%
“…30 These findings seem to be in line with other studies that examined community-based samples, including TGD youths. [31][32][33] Other reports could not demonstrate differences in tobacco habits, as shown in a secondary analysis of the Population Assessment of Tobacco and Health study (AOR, 1.19; 95% CI, 0.75-1.89) 34 and substudies of the BRFSS 2016 (AOR, 0.87; 95% CI, 0.54-1.41) 35 and the BRFSS 2014 (AOR, 1.20; 95% CI, 0.84-1.72). 36 A study of cancer survivors from the BRFSS 2014-2018 25 found that transgender men had significantly lower prevalence of smoking compared with cisgender men (AOR, 0.09; 95% CI, 0.02-0.38) and cisgender women (AOR, 0.10; 95% CI, 0.03-0.43), whereas transgender women did not differ significantly in smoking prevalence compared with cisgender women (AOR, 0.79; 95% CI, 0.28-2.21) or cisgender men (AOR, 0.69; 95% CI, 0.25-1.96).…”
Section: Smokingmentioning
confidence: 99%
See 3 more Smart Citations